Areas and Applications of Artificial Intelligence in Law - Farida Abdelfattah Rady; Sally Awad Elsakka (International Journal of Law Research and Studies, 2024)
Artificial intelligence is a branch of computer science that is concerned with using intelligent technologies to accomplish tasks that require human intelligence to complete. It aims to program machines to be able to simulate human intelligence, allowing them to think and act like humans. This term is used to refer to any device that can exhibit characteristics similar to the human mind, such as learning and problem solving. Artificial intelligence is characterized by its ability to choose the best procedures to achieve a specific goal with the best possible chance, and also includes the feature of machine learning. The importance of artificial intelligence lies in its ability to have a significant impact in many sectors around the world, giving companies a significant competitive advantage. There are some uses that highlight its importance, such as healthcare, agriculture, transportation, buying and selling products, managing renewable energy systems, and manufacturing. This research deals with the fields and applications of artificial intelligence in law.